Input-Based and Time-Based Models of International Adjustment: Meta-Analytic Evidence and Theoretical Extensions - Bhaskar-Shrinivas, Purnima; Harrison, David A.; Shaffer, Margaret A.; Luk, Dora M. (Academy of Management Journal, 2005)
Integrating work on international assignments and domestic stress, we conducted meta-analyses of over 50 determinants and consequences of expatriate adjustment using data from 8,474 expatriates in 66 studies. We also examined the trajectory of adjustment over time, and time as a moderator of adjustment effects. Results emphasize the centrality, criticality, and complexity of adjustment, strongly supporting Black, Mendenhall, and Oddou's (1991) model. Structural modeling of proposed model extensions showed that adjustment uniquely affects job satisfaction, withdrawal cognitions, and performance.